Allegoria: fu vera gloria? - Andrea Pinotti (Aisthesis, 2012)
Gadamer and many others considered Benjamin as the upholder of the allegoric and the advocate of allegory both as an object and as a method, opposed to the predominance of the symbolic, initiated in the philosophy of art by Goethe. My paper aims at verifying whether it is really possible to speak of a dismissal of the symbol in Benjamin’s discourse, intimately imbued as it is with Goethe’s morphology.